Fairy tales and psychoanalytic listening in early childhood education (Research, Society and Development, 2022)
Early Childhood Education is the first stage of schooling in Brazil. During this school period, the use of the fairy tale literary genre becomes relevant by promoting a school education work that is implied by a therapeutic perspective. Based on this premise, the issue of how to handle fairy tales based on narrative and expanded psychoanalytic listening in early childhood education units was raised. To answer this question, the handling of fairy tales by the expanded psychoanalytic clinic in early childhood education will be presented; strategies to contribute to an educational process that is tuned to the psychic needs in early childhood; stimuli of recurrence to fantasy resources, aiming at the resignification of conflicts intrinsic to the human condition. In this work, we resorted to a bibliographic review of the works of Bettelheim (1977/2019) and other contemporary authors that deal with fairy tales. Therefore, it was considered that the use of fantasy in Early Childhood Education is fundamental due to the place that the school institution occupies in early childhood, which is complementary to that of the family.